Introduction - Jodhka, Surinder S.; Hofner, Lara; Vaid, Divya; Baumann, Benjamin; Bultmann, Daniel; Vakulabharanam, Vamsi (Global handbook of inequality, 2024)
The chapter offers an introduction to the handbook and a broad overview of how the subject of inequality has evolved over the past century and more. Inequality is a pervasive fact of human life almost everywhere. Its forms, patterns, and magnitudes have indeed seen many changes, but it has continued to persist. In popular imagination, inequality is often viewed purely in economic terms. While differences in income and wealth are indeed indicators of inequality, they by themselves do not define or explain it. For a better understanding of the subject, we argue that inequality is fundamentally about power and domination; it is about the patterns of distribution of what is valued in society. Economic indices matter because they too bear symbolic value. Inequality also has plural axes, shaped by context and history. Hierarchies based on ascription do not go away with the arrival of capitalism. Besides the persistent significance of phenomena such as caste, race, and ethnicity, colonial histories continue to shape and structure the global economy of the twenty-first century.